Antecedents and Consequence of Trust - Commitment Towards Artificial Based Customer Experience (Revista Galega de Economía)
With the advent of AI, consumer-brand interactions are undergoing a dramatic transformation (Prikshat, Malik, and Budhwar, 2021). The consumer experience that AI aids is a least explored area of study. This research aims to examine how AI may be used in retail to enhance the purchasing experience for AI users. With the trust-commitment theory and the service quality model as our inspiration, we put out a theoretical framework. Customers who have used a YouTube service powered by artificial intelligence were sent an online survey. Partial least squares-structural equation modeling was used to analyze the data (n=301 replies). Trust and relationship commitment was shown to play a pivotal role in moderating the connections between customers' evaluations of service convenience, individualization, and quality. We also discovered that trust is not the only factor that substantially influences relationship commitment and that relationship commitment acts as a mediator between service quality and AI-enabled customer experiences. This research fills a gap in the literature by identifying the direct influence of perceived convenience, personalization, and service quality on AI-enabled customer experience and the intermediary effects of trust and relationship commitment. Further, the research has real-world consequences for businesses that want to apply AI in the services they provide to YouTube subscribers.